Antimicrobial agents used in the control of periodontal biofilms: effective adjuncts to mechanical plaque control? - Ricardo Palmier Teles; Flavia Rocha Fonseca Teles (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The control of biofilm accumulation on teeth has been the cornerstone of periodontal disease prevention for decades. However, the widespread prevalence of gingivitis suggests the inefficiency of self-performed mechanical plaque control in preventing gingival inflammation. This is particularly relevant in light of recent evidence suggesting that long standing gingivitis increases the risk of loss of attachment and that prevention of gingival inflammation might reduce the prevalence of mild to moderate periodontitis. Several antimicrobials have been tested as adjuncts to mechanical plaque control in order to improve the results obtained with oral home care. Recent studies, including meta-analyses, have indicated that home care products containing chemical antimicrobials can provide gingivitis reduction beyond what can be accomplished with brushing and flossing. Particularly, formulations containing chlorhexidine, mouthrinses containing essential oils and triclosan/copolymer dentifrices have well documented clinical antiplaque and antigingivitis effects. In vivo microbiological tests have demonstrated the ability of these antimicrobial agents to penetrate the biofilm mass and to kill bacteria growing within biofilms. In addition, chemical antimicrobials can reach difficult-to-clean areas such as interproximal surfaces and can also impact the growth of biofilms on soft tissue. These agents have a positive track record of safety and their use does not seem to increase the levels of resistant species. Further, no study has been able to establish a correlation between mouthrinses containing alcohol and oral cancer. In summary, the adjunct use of chemical plaque control should be recommended to subjects with well documented difficulties in achieving proper biofilm control using only mechanical means.